Kemudahan Penggunaan Paylater, Pembelian Impulsif, Kontrol Diri dan Literasi Keuangan Terhadap Perilaku Pengelolaan Keuangan Pribadi: Survei Terhadap Generasi Z di Kota Surakarta - Aflintang Wahyu Nur A’ni; Erma Setiawati (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
The rapid development of digital technology has increased the use of digital financial services, particularly paylater payment methods, which are widely used by Generation Z. The convenience of transactions offered by these services has the potential to influence personal financial management behavior. This study aims to examine the effects of paylater ease of use, impulsive buying, self-control, and financial literacy on the personal financial management behavior of Generation Z in Surakarta City. This research employs a quantitative associative approach using primary data collected through questionnaires distributed to 150 Generation Z respondents selected using purposive sampling. Data analysis was conducted using multiple linear regression with the assistance of SPSS software. The results indicate that paylater ease of use, impulsive buying, and self-control do not have a significant effect on personal financial management behavior. Meanwhile, financial literacy has a positive and significant effect on personal financial management behavior. This study emphasizes that financial literacy is the most important factor in shaping Generation Z’s personal financial management behavior amid the rapid growth of digital financial services.